Regulatory Role of Hexokinase 2 in Modulating Head and Neck Tumorigenesis - Li, Wan-Chun; Huang, Chien-Hsiang; Hsieh, Yi-Ta; Chen, Tsai-Ying; Cheng, Li-Hao; Chen, Chang-Yi; Liu, Chung-Ji; Chen, Hsin-Ming; Huang, Chien-Ling; Lo, Jeng-Fan; Chang, Kuo-Wei (Frontiers in Oncology, 2020)
To support great demand of cell growth, cancer cells preferentially obtain energy and biomacromolecules by glycolysis over mitochondrial oxidative phosphorylation (OxPhos). Among all glycolytic enzymes, Hexokinase (HK), a rate-limiting enzyme at the first step of glycolysis to catalyze cellular glucose into glucose-6-phosphate, is herein emphasized. Four HK isoforms, HK1-HK4, were discovered in nature. It was shown that HK2 expression is enriched in many tumor cells and correlated with poorer survival rates in most neoplastic cells. HK2 mediated regulations for cell malignancy and mechanistic cues in regulating head and neck tumorigenesis, however, is not fully elucidated. Cellular malignancy index such as cell growth, cellular motility, treatment sensitivity as well as molecular alterations were determined in HK2 deficient Head and Neck Squamous Cell Carcinoma (HNSCC) cells. By using various cancer databases, HK2, but not HK1, positively correlates with HNSCC progression in a stage-dependent manner. A high HK2 expression was detected in head and neck cancerous tissues compared with their normal counterparts, both in mouse and human subjects. Loss of HK2 in HNSCC cells resulted in reduced cell (in vitro) and tumor (in vivo) growth as well as decreased Epithelial Mesenchymal Transition (EMT) mediated cell movement; in contrast, HK2 deficient HNSCC cells exhibited greater sensitivity to chemotherapeutic drugs cisplatin and 5-fluouracil but are more resistant to photodynamic therapy indicating that HK2 expression could selectively define treatment sensitivity in HNSCC cells. At the molecular level, it was found that HK2 alteration drove metabolic reprogramming toward OxPhos and modulated oncogenic Akt and mutant TP53 mediated signals in HNSCC cells. In summary, present study showed that HK2 suppression could lessen HNSCC oncogenicity, modulate therapeutic sensitivity thereby being an ideal therapeutic target for HNSCCs.